Navigating Uncharted Waters: First-Generation Native Hawaiian College Students in STEM. (November 2019) - Allaire, Franklin S.
This qualitative study explored the experiences of 10 Native Hawaiian members of Hawai'i's science, technology, engineering, and mathematics (STEM) community to understand how they navigate their cultural and professional identities. This article explores one of the major themes—being first-generation college students—and the narrators' inspirations, influences, and challenges as first-generation college students in STEM-related degree programs. Within this context, the participants explore the impact of support networks, going beyond the educational level of their parents, as well as feelings of inferiority, tokenism, and marginalization as one of the few Native Hawaiian students in STEM degree programs. These findings are substantial in that they offer understanding related to a distinct racial/ethnic minority that is underrepresented in higher education and the sciences.